Involvement of the millennial generation in boosting the digital economy in the era of society 5.0: literature study - Sigit Purwoko (Universitas Wiralodra, 2023)
The purpose of this research is to find out how the involvement or role of the millennial generation is in boosting the digital economy in the era of society 5.0. This research method uses a literature review study by searching for articles using search engines such as EBSCO, ScienceDirect, and Proquest. Articles were searched using